Toxicity of gamma-benzene hydrochloride (y-bhc) to oreochromis niloticus (pisces: cichlidae) (2000)
The toxicity of gamma-benzene hydrochloride (y-BHC) to Oreochromis mlolicus was evaluated in a static bioassay system A various concentrations and ponods of exposure, changes in behavioural responses and ortahbes were recorded in the test fish, while no such responses or any molality was recorded in the control fish throughout the period of the experiment increasing concentration and periods of exposure to y-BHC caused uncoordinated movements, erratic swimming behavior and extreme dullness prior to death of the lest fish. There are progressive heamoconcentration, hyperproteinaemia, hypernatraemia, decreased plasma cabon concentration, hypoglycaemia and increased plasma levels of ALP, AST and ALT will increasing concentration of y- BHC and period of exposure of test fish Death of test fish pccued cathest in the highest concentration of y- BHC(200ppm) and with increasing ponods of exposure postmortem lesions observed in the test fish include haemorrhagic and necrotic enlentis and myocarditis, hepalocellular degeneration and necrosim and non-suppurative meningoencephalitis it is concluded that y-BHC is very toxic to O.nilolicus, causing severed ncule denydration,haemoconcentration, organ damage and death. Hence, it is suggested that the use of y-BHC to properly controlled and regulated by appropriate legislation in order to prevent its bioaccumulation in the environment and immnent disastrous effect on the ecosystem